PEMANFAATAN FRAKSI ETANOL DAUN JARUM TUJUH BILAH (Pereskia bleo (Kunth) D.C) SEBAGAI INHIBITOR XANTIN OKSIDASE DALAM PEMBENTUKAN ASAM URAT - Sarwawan, Ade Putri Hawiyah; Sitorus, Saibun; Gunawan, Rahmat (JURNAL ATOMIK; Vol 4 No 1 (2019), 2019)
This research was conducted to determine the content of secondary metabolite contained in the extract and ethanol fraction of â€œJarum tujuh bilahâ€ leaves ( Pereskia bleo (Kunth) DC) and and inhibition of xanthine oxidase activity obtained from the isolation of cow's milk. The xanthine oxidase activity is measured at a wavelength of 290 nm. The results of this research indicate that in the ethanol extract and fraction of â€œjarum tujuh bilahâ€ leaves have the secondary flavonoids, alkaloids and phenolic compounds. The highest inhibition of xanthine oxidase activity in the ethanol extract of â€œjarum tujuh bilahâ€ leaves was 91.67%, while the inhibition of allopurinol was 50% and the ethanol fraction of â€œjarum tujuh bilahâ€ leaves was seven blades by 90%.